2007
DOI: 10.3748/wjg.v13.i40.5351
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fistula after pancreaticoduodenectomy: A comparison between the two pancreaticojejunostomy methods for approximating the pancreatic parenchyma to the jejunal seromuscular layer: Interrupted vs continuous stitches

Abstract: AIM:The purpose of this study is to find a better operative technique by comparing interrupted stitches with continuous stitches for the outer layer of the pancreaticojejunostomy, i.e., the stitches between the stump parenchyma of the pancreas and the jejunal seromuscular layer, and other risk factors for the incidence of pancreatic leakage. METHODS:During the period January 1997 to October 2004, 133 patients have undergone the end-to-side and duct-to-mucosa pancreaticojejunostomy reconstruction after pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
0
32
1
2
Order By: Relevance
“…When compared with other studies [27][28][29][30][31][32][33], we found that the results of present study were much better and very encouraging. Except of the above-mentioned, the advantages of our technique are: (1) simple, only two to three transpancreatic U-sutures are placed; (2) easy, no need of isolation of long segment of remnant pancreas as described by Peng et al [25], pancreatic stump could be easily invaginated into the jejunum loop through straining the Usutures; (3) rapid, the median time to perform pancreaticojejunostomy using this technique was only 13.3 min (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…When compared with other studies [27][28][29][30][31][32][33], we found that the results of present study were much better and very encouraging. Except of the above-mentioned, the advantages of our technique are: (1) simple, only two to three transpancreatic U-sutures are placed; (2) easy, no need of isolation of long segment of remnant pancreas as described by Peng et al [25], pancreatic stump could be easily invaginated into the jejunum loop through straining the Usutures; (3) rapid, the median time to perform pancreaticojejunostomy using this technique was only 13.3 min (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 95%
“…The median duration of surgery of 88 patients was 3.8 h (range 3-6.5) and the median time to perform pancreaticojejunostomy was 13.3 min (range [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median blood loss was 750 ml (range 300-1,800), 36 of 88 patients needed transfusion and the median blood transfusion for 56 patients was 380 mL (range 200-1,200).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing both types of anastomosis, duct-to-mucosa and invagination, the duct-to-mucosa anastomosis was initially described as safer and with a significantly lower rate of fistula [20,21] . Subsequently, in 2003 a prospective randomized trial [8] found PF in 14% of patients: 13% in the group with duct-to-mucosa anastomosis and 15% in the group with anastomosis by invagination, although the difference was not significant.…”
Section: Pj By Invaginationmentioning
confidence: 99%
“…Continuous duct-to-mucosa anastomosis was described as being safer and as having a significantly lower leakage rate [16,17]. However, a prospective randomized clinical trial found it to be favored in low-risk patients with a dilated pancreas duct or firm fibrotic pancreas, whereas the invagination technique was better for highrisk patients with small ducts or a soft friable pancreas [18].…”
Section: Pancreatojejunostomymentioning
confidence: 99%